2014
DOI: 10.1002/ange.201308794
|View full text |Cite
|
Sign up to set email alerts
|

Proximity‐Enabled Protein Crosslinking through Genetically Encoding Haloalkane Unnatural Amino Acids

Abstract: The selective generation of covalent bonds between and within proteins would provide new avenues for studying protein function and engineering proteins with new properties. New covalent bonds were genetically introduced into proteins by enabling an unnatural amino acid (Uaa) to selectively react with a proximal natural residue. This proximity-enabled bioreactivity was expanded to a series of haloalkane Uaas. Orthogonal tRNA/synthetase pairs were evolved to incorporate these Uaas, which only form a covalent thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 17 publications
0
45
0
Order By: Relevance
“…A survey of the literature reveals that most engineered cysteine disulfides give a Tm increase around 5°C, although there are a few cases where a more than 10°C increase in Tm is observed (27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Interestingly, in work related to that described here, Xiang et al (13) demonstrated that halogen-containing NCAAs with relatively long side chains are capable of forming a covalent linkages with a Cys residue and showed that they improved the thermal stability of an affibody by 13°C in vitro.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…A survey of the literature reveals that most engineered cysteine disulfides give a Tm increase around 5°C, although there are a few cases where a more than 10°C increase in Tm is observed (27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Interestingly, in work related to that described here, Xiang et al (13) demonstrated that halogen-containing NCAAs with relatively long side chains are capable of forming a covalent linkages with a Cys residue and showed that they improved the thermal stability of an affibody by 13°C in vitro.…”
Section: Discussionmentioning
confidence: 72%
“…These longer and more flexible linkages should make it much easier to cross-link sites within proteins. Indeed, it has recently been shown that electrophilic amino acids with extended structures can selectively stabilize proteins and protein complexes by intra-and intermolecular cross-links, respectively (13,(23)(24)(25). However, the use of electrophilic NCAAs to form noncanonical cross-links in a bacterial selection system can be complicated by cellular toxicity, irreversible reactions, reaction rates, and scavenging by intracellular nucleophiles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One powerful approach for this purpose is (photo-)cross-linking [32,33]. Previous efforts have used tag-mediated labeling [34,35] or unnatural amino acid mutagenesis [36][37][38] to introduce (photo-)cross-linkers to proteins of interest artificially expressed in cells. However, the utility of the (photo-)cross-linking approach should be greatly enhanced if it can be applied to endogenous proteins.…”
Section: Photo-cross-linking Of Protein Complexesmentioning
confidence: 99%